Performing Dônga. The restorative benefits of ritual stick duelling in Mursi (Mun) - LaTosky, Shauna; Olibui, Olisarali (Antropologia Pubblica, 2024)
Dônga, an ancient form of stick duelling practiced by the Mursi (Mun) 1 of southwest Ethiopia is both a competitive martial art and ritual performance through which the tensions, predicaments and conflicts of society are confronted and resolved. As articulated in the anthropological literature, dônga constitutes a socio-political mechanism that promotes societal stability and prevents the disintegration of social relations (Turton 1973; 2002). In this paper we offer a view that expands on explanations of dônga in socio-political terms by looking also at its ritual, gendered and aesthetic aspects, and how it is that dônga has recently come into direct dialogue with the contemporary political events unfolding in South Omo through the first-ever Mursi-authored performance about dônga. Set against the dramatic backdrop of the arrival of Ethiopian military in Mursiland in November 2019, the original script, written by Olisarali Olibui and Tesfahun Haddis, illustrates the preoccupations of every Mursi at this time: the brutalities during the government’s forced disarmament campaign, and their uncertain future as pole-wielding pastoralists. We consider dônga as one of the central metaphors for the predicaments of Mursi today, as both the performative practice of dônga and the principles it stands for – the protection of rights and restoration of societal unity – have come under threat. The suppression of dônga through the use of political rhetoric since 2012 has been ramped up at the same time as state military forces have disarmed the Mursi.